Proceedings of the 12th International Conference on Business and Management Research (ICBMR 2018) 2019
DOI: 10.2991/icbmr-18.2019.27
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Organizational Commitment and The Moderating Role of Service Climate

Abstract: This study aims to predict the effect of job satisfaction on knowledge sharing behavior. At the same time, it aims to predict the moderation role of service climate as well as the mediation role of organizational commitment. Based on the results of this research, organizational commitment has a significant positive effect on knowledge sharing behavior. Based on this, organizational commitment has a full mediation effect on the influence of job satisfaction on knowledge sharing behavior. Service Climate does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…Our study analysis is in line with the statement of Lona et al (2020), which stated that affective commitment is unsuitable mediator on performance, when the predictor is not optimal. In the other side, our finding is not in line with several literature (Arifin et al 2020;Kawiana 2018;Raveendran and Gamage 2019;Supartha, Sihombing, and Sukerti 2019), which stated that affective commitment is strong mediator on performance, especially in bureaucracy levels.…”
Section: Resultscontrasting
confidence: 99%
“…Our study analysis is in line with the statement of Lona et al (2020), which stated that affective commitment is unsuitable mediator on performance, when the predictor is not optimal. In the other side, our finding is not in line with several literature (Arifin et al 2020;Kawiana 2018;Raveendran and Gamage 2019;Supartha, Sihombing, and Sukerti 2019), which stated that affective commitment is strong mediator on performance, especially in bureaucracy levels.…”
Section: Resultscontrasting
confidence: 99%
“…Such as a mediating role of organizational commitment (Cao et al, 2020;Supartha et al, 2018), there have been several empirical studies that show a mediating role of job satisfaction (Devonish, 2018;Dinc, 2017;Valaei and Razaei, 2016;Saleem and Saleem, 2014) between different HRM factors. However, any study conducting the mediating role of job satisfaction between compensation structure and organizational commitment is sparse.…”
Section: Analysis Using Semmentioning
confidence: 99%
“…The job satisfaction-service quality association: the mediating role of organizational commitment As discussed earlier, which shown job satisfaction to significantly and positively affect employees' OC (Chegini et al, 2019;Gopinath, 2020;Mapuranga et al, 2021;Supartha et al, 2019). In this dynamic, employees who experience a good degree of job satisfaction will likely to develop a strong sense of commitment to their organization (Mowday et al, 1982).…”
Section: Organizational Commitment and Service Qualitymentioning
confidence: 96%
“…Job satisfaction was positively associated with affective commitment (Valaei and Rezaei, 2016). Supartha et al (2019) in their study of four-star hotels in Bali, found that job satisfaction strongly influenced OCwhen job satisfaction increased, OC increased as well. Gopinath (2020) examined the effect of job satisfaction on the OC of 145 academic staff in India and discovered that job satisfaction significantly predicted OC.…”
Section: Job Satisfaction and Organizational Commitmentmentioning
confidence: 99%